Paradigma Pengembangan Pengajaran Bahasa Arab: Telaah Integratif Linguistik Dan Budaya Lokal - Muhammad Birrul Walidaen; Dimas Prayana Rizki; Karuniawan Ilhamsyah; Fathul Maujud (Kartika: Jurnal Studi Keislaman, 2026)
Arabic language learning in Indonesia faces significant challenges in the form of low student motivation and the lack of relevance of teaching materials, which are often non-contextual and overly oriented toward rigid grammatical rules. This study aims to comprehensively elaborate on the nature, urgency, theoretical foundations, systematic procedures, and innovations in the development of Arabic teaching materials that are adaptive to modern instructional needs. Through a review of the Research and Development methodology using procedural models such as ADDIE, 4-D, and Borg & Gall, the development is carried out systematically from needs analysis to expert validation and field testing. The results of the study show that the effectiveness of teaching materials is determined by the integration of four main principles: socio-cultural, psychological, linguistic, and educational. Innovation through a contrastive approach and the integration of local culture has proven effective in minimizing first language interference and increasing students’ emotional engagement. Furthermore, the use of digital technology, such as Android-based mobile learning and interactive media, significantly improves learning independence and the achievement of language competencies. This study concludes that the development of teaching materials that are systematic, innovative, and technology-based is a crucial instrument for transforming Arabic language education in Indonesia to be more communicative, effective, and transformative